Prevalencia de caries y pérdida prematura del primer molar permanente en niños de 6 - 12 años del Colegio Augusto Freyre García - Armas Garcia, Brian Ayrton (2025)
This research study highlights that there is a high incidence of tooth decay in children in our region. Given that the first molar is the first tooth to erupt, it is exposed to tooth decay, and when it causes pain, parents take their children to health clinics, where the only thing that is done is to extract the teeth without providing any other type of care. Therefore, it is important to take preventive measures to avoid dental caries and the subsequent premature loss of the first permanent molar. Objective: To determine the prevalence of caries and premature loss of the first permanent molar in children aged 6 to 12 years at the Augusto Freyre School. Population: The population consisted of pupils in grades 1 to 6 of primary school in sections A and B of the Augusto Freyre School, with a total sample of 258 children between the ages of 6 and 12. Methodology: The research was quantitative, non-experimental, descriptive and correlational. Results: Schoolchildren have a very low prevalence of caries (80.6%), while 18.7% have a low level and only 0.6% have a moderate level. Likewise, schoolchildren present premature loss of the first molar in 2.6% of cases. However, 97.4% do not present premature loss of the first molar. Applying Fisher-Freeman- Halton's exact test yielded a value of F=48.036 with p<0.001, lower than the established significance level (α=0.05), which demonstrates that there is a significant relationship. Conclusion: The research study concludes that there is a statistically significant association between the prevalence of dental caries and the premature loss of the first permanent molars in the schoolchildren evaluated.